Assistance of Traditional Schools of Games and Sports as an Effort to Improve Psychomotors SLB Students Bangkalan District - Khoirul Anwar; Miranti Widi Andriani; Ruski; Ihwan Firmansyah; Agus Himawan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of the activity is to provide direct understanding to teachers regarding the preparation, implementation and evaluation of traditional games and sports schools as an effort to improve the psychomotor skills of special school students. The method used is mentoring and workshops on traditional games and sports. The results of the mentoring activities for traditional games and sports schools as an effort to improve the psychomotor skills of the Keleyan State Special School students in Bangkalan Regency have the aim of combining traditional games in learning. The benefits of traditional games and sports for SLB students include optimizing physical development, stimulating movement skills and increasing endurance that is useful for life. SLB teachers also need to understand the stages in learning traditional games for SLB students. Conclusion: mentoring schools for traditional games and sports has succeeded in helping special schools have the opportunity to improve their psychomotor and moving body functions for their lives.